The Potential Values of Riyadhoh Improving the Quality of Learning of Students - Elqaweliya, Bela; Satori, Djam’an; Nurdin, Diding; Prihatin, Eka; Nuphanudin, Nuphanudin (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2023)
Students are always trying to improve the quality of their learning outcomes. One of the aspirations of the students is riyadhoh. It plans to improve the quality of learning outcomes in terms of intellectual, emotional, and spiritual intelligence. The purpose of this study was to investigate information about the potential values ​​of riyadhoh that are believed to improve the quality of student learning outcomes. This study used a systematic review of research findings related to the potential values ​​of riyadhoh to improve the intellectual, emotional, and spiritual intelligence of students. The technique of this study was riyadhoh's meta-synthesis analysis, which can improve the quality of student learning outcomes and make students successful. The results of this study show that riyadhoh can improve the academic performance of students from the perspective of intellectual, emotional, and spiritual intelligence and make them successful.